Is isolation of extensively drug resistant tuberculosis (XDR-TB) patients in South Africa ethically and legally justifiable? - Khumalo, Charmaine Slindile (My University, 2021)
South Africa (SA) is reported as having one of the highest burdens of tuberculosis (TB) in the world. Drug resistant TB is a major global epidemic, with 500,000 cases occurring annually. In 2006, extensive drug resistant TB (XDR-TB) cases were first reported in SA. This particular strain of Mycobacterium tuberculosis has proven to be the most difficult to treat as it requires a more complex treatment regime. The prevention and treatment of XDR-TB are of paramount importance not only in SA, but worldwide. This study outlines the magnitude of the need to treat XDR-TB by isolation. Isolation requires legal and ethical analysis, as this is not a norm in the treatment of communicable diseases. The South African government’s legal and moral responsibilities were critically analysed in this study. Several laws were analysed with relation to isolation as an intervention for XDR-TB treatment. The bioethical theories that were analyzed included deontology, utilitarianism, virtue ethics, communitarianism, and Ubuntu ethics. Isolation of XDR TB patients was also examined through the four principles of bioethics: respect for patient autonomy and informed consent; beneficence; non-maleficence; and justice. The use of these bioethical perspectives illustrated the requirement for isolation as an intervention for the treatment of XDR-TB
A research report submitted in fulfilment of the requirements for the degree Masters of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021